LAB studio model: Developing external networks for learning entrepreneurship in higher education - Kari-Pekka Heikkinen; Ulla-Maija Seppänen; Jouko Isokangas (University of Aberdeen, School of Education, 2015)
This article summarises a study of the purposefulness, structure and amount of external learning networks formed during an interdisciplinary higher education programme based on a LAB studio model. The LAB studio model is a learning model, which develops connections between working-life based problems and the recognition and development of the related business prototypes and startups. The LAB studio model is theoretically grounded in a constructivist view of learning with a project-based education at its core and has a key goal of educating entrepreneurship competences. The data for the study was collected through semistructured interviews with six student teams (N=35) during May 2015. The data analysis took place through mixed methods, which as a method focuses on collecting, analysing, and mixing both quantitative and qualitative data. Findings show that the LAB studio model challenges and enables students to develop new learning networks external to the traditional university environment. New learning networks are created due to the demanding problem - solving process used in the teaching activities. Overall, the education programme broke down barriers between the education environment and external business environment through the establishment of learning networks. In conclusion, the learning networks formed during the education programme were wide-ranging, and the role of students was active and selfdirective. Furthermore, we suggest that social capital was increased during the educational process.